Mengembangkan Sikap Sosial Anak Menggunakan Teknik Intervensi Mikro Di Sanggar Pelita - Wigar Fakih Izati; Randa Putra Sinaga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Every child has a problem with the social sensitivity that is around him, be it school, environment, or family. Social attitude is one aspect that needs to be developed to improve children's social skills. Social attitude is an individual's awareness that determines real actions to behave in a certain way towards others and emphasizes social goals rather than personal goals in public life. Attitude is a tendency to approach or avoid, positive or negative towards various social conditions in the environment they are in, whether it be institutions, individuals, situations, ideas, concepts and so on. If you look closely, almost all definitions of attitude have the same view. Community service is a form of dedication by students or lecturers by pouring knowledge, experience and other things that have been obtained to go down directly to the community. The author carries out community service which is one part of the author's Field Work Practice. This community service is carried out at the Pelita Studio. The author carries out this activity by setting the object of service, namely one student aged 12 years and has attended junior high school. Implementation is used with the Micro Intervention method.